(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
2,4-D(2,4-Dichlorophenoxyaceticacid) is a common herbicide in agriculture field. It has moderately toxic effect on mammals.2,4-D is available either in salt or ester formulations for field level use .Although no specific antidote available for this herbicide, forced alkaline diuresis is one of the modalities of treatment to promote early excretion of toxin through kidney and minimize its complications .Other management are essentially supportive measure and prevention of possible complications like aspiration pneumonia .There are a numbers of complications that are reported in varying degree .It affects skeletal muscle ,cardiovascular ,gastrointestinal , renal ,central and peripheral nervous system. Here we report a case who developed unusual complications like leukopenia, hypomagnesemia, proximal muscle weakness after consumption of 2,4-D after suicidal intent.